Sensorless control of direct-driven PMSG wind turbines using NPIC and MRAS observer. (11th January 2023) - Elgharib, Ahmed Omar; Benzaouia, Soufyane; Naamane, Aziz
This article presents a sensorless control technique of a direct driven permanent magnet synchronous generator wind turbine. The proposed sensorless approach uses an MRAS observer for generator rotational speed estimation. This latter needs only three phase voltage and current measurements provided by the cheapest electrical sensors. There are two main objectives in this article: first one is extracting and achieving the maximum power point using a vector control technique based on nonlinear proportional integral controller, while the second one is avoiding the use of mechanical speed sensor by utilising MRAS observer for cheaper implementation. Such an article shows the performance of the whole system by using the proposed control strategy with and without speed sensor. The obtained results prove the efficiency and effectiveness of the developed approach.